Impact of a Brief, Bystander Bullying Prevention Program on Depressive Symptoms and Passive Suicidal Ideation: A Program Evaluation Model for School Personnel. Issue 1 (July 2020) - Midgett, Aida; Doumas, Diana M.; Peralta, Claudia; Bond, Laura; Flay, Brian
The purpose of this article is to present a study that can serve as a model of program evaluation for school personnel that can be used to improve services and demonstrate program efficacy to key stakeholders. The study presented in this article evaluated the impact of a brief, bystander bullying program ("stealing the show, " "turning it over, " "accompanying others, " and "coaching compassion, " [STAC]) on depressive symptoms and passive suicidal ideation among middle school students in a rural, low-income community ( N = 130). This topic was selected as there is limited research examining the efficacy of bystander programs on improving mental health outcomes for students trained to intervene. Results of the study indicated students trained in the STAC program reported reductions in depressive symptoms and passive suicidal ideation at a 6-week follow-up compared with an increase in symptoms reported by students in the control group. We discuss these findings and the use of program evaluation by school personnel to support prevention programming.